MAYSIR ELEMENT ANALYSIS IN BINARY OPTION PLATFORM CASE STUDY OF IQ OPTION APPLICATION - Baldad Muhammad Syarifati; Maya Panorama (International Journal Labs, 2022)
Binary options or more often referred to as binary options are financial instruments that are not very familiar to the public at first. However, it became familiar in the community after the recent viral case of fraud under the guise of investment was revealed. This study aims to analyze the elements of gambling (maysir) in the binary options platform. The method applied in this study is a normative legal approach using qualitative methods derived from secondary data. This study examines binary options using the desk research method. Secondary research or desk research methods are research methods whose analysis is through comprehensive library research from secondary industrial data and academic sources. Based on the systematic transaction in the binary options platform, we consider that the practice of binary options contains elements of gambling, namely; there are parties who bet (compete), there are assets at stake, there are winning and losing parties, and the winning party is entitled to the assets of the losing party. This study concludes that binary options are financial instruments that are identical to gambling or can be said to be hidden gambling. This is because transactions on binary options contain four gambling criteria that have been agreed upon by the scholars.